Time trends of variability in disease activity in systemic lupus erythematosus - Tsutomu Takeuchi; Yoshiya Tanaka; Rangi Kandane-Rathnayake; Ning Li; Sang-Cheol Bae; Zhanguo Li; Shereen Oon; Vera Golder; Mandana Nikpour; Masayoshi Harigai; Yi-Hsing Chen; Zhuoli Zhang; et al. (Lupus Science and Medicine)
Objective Disease activity both between and within patients with SLE is highly variable, yet factors driving this variability remain unclear. This study aimed to identify predictors of variability in SLE disease activity over time.Methods We analysed data from 2930 patients with SLE across 13 countries, collected over 38 754 clinic visits between 2013 and 2020. Clinic visit records were converted to panel data with 1-year intervals. The time-adjusted mean disease activity, termed AMS, was calculated. The yearly change in AMS, denoted as ΔAMSt, was regressed onto AMSt−1 and other potential predictors using random-effects models. Some variables were split into a person-mean component to assess between-patient differences and a demeaned component to assess within-patient variability.Results Overall, variability in SLE disease activity exhibited stabilisation over time. A significant inverse relationship emerged between a patient’s disease activity in a given year and variability in disease activity in the subsequent year: a 1-point increase in person-mean disease activity was associated with a 0.27-point decrease (95% CI −0.29 to –0.26, p<0.001) in subsequent variability. Additionally, a 1-point increase in within-patient disease activity variability was associated with a 0.56-point decrease (95% CI −0.57 to –0.55, p<0.001) in the subsequent year. Furthermore, each 1-point increase in the annual average time-adjusted mean Physician Global Assessment was associated with a 0.08-point decrease (90% CI −0.13 to –0.03, p=0.002) in disease activity variability for the following year. Prednisolone dose and the duration of activity in specific organ systems exhibited negative and positive associations, respectively, with disease activity variability in the subsequent year. Patients from less affluent countries displayed greater disease activity variability compared with those from wealthier nations.Conclusion Disease activity tends to be less variable among patients with higher or more variable disease activity in the previous year. Within-patient variability in disease activity has a stronger impact on subsequent fluctuations than differences between individual patients.